Hands-on Activities Vs Multimedia Content in Science in Developing Pre-service Teachers’ Competence - Singh, Vijay P.; Husain, Ahrar (SCHOOL SCIENCE, 2017)
This paper reports the finding of our study with the use of hands-on activities and multimedia science content in training of pre-service teacher trainees of elementary level. A pre- and post-test design was chosen for the study. Two groups of trainees formed the experimental group 1 (PTHA, N=39) and group 2 (PTMC, N=34). The experimental groups were oriented on some selected chemistry related content of NCERT science textbooks. The interventions were made by the first Investigator on second year trainees of District Institute of Education and Training of East and North East districts of Delhi. The pre- and post-test scores of both the groups were compared by subjecting the data with appropriate statistics. The analysis of data indicates that the post-test gain scores of both the experimental groups were improved. However, the group treated with hands-on activities showed a marked and significant improvement in their pedagogical content knowledge of the topics covered in the intervention